2013
DOI: 10.1038/labinvest.2012.153
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TNF-α-converting enzyme in fibroblasts augments dermal fibrosis after inflammation

Abstract: TNF-a-converting enzyme (TACE) can cleave transmembrane proteins, such as TNF-a, TNF receptors, and epidermal growth factor receptor (EGFR) ligands, to release the extracellular domains from the cell surface. Recent studies have suggested that overexpression of TACE may be associated with the pathogenesis of inflammation and fibrosis. To determine the roles of TACE in inflammation and fibrosis, TACE transgenic (TACE-Tg) mice, which overexpressed TACE systemically, were generated. As the transgene-derived TACE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…It was previously demonstrated that the phosphorylation of EGFR controls its subcellular distribution in 3D-MDCK cultures, allowing it to modulate epithelial morphogenesis (Cotton et al, 2013). Moreover, PMA phosphorylates and transactivates EGFR in glioblastoma cells and in dermal fibroblasts (Amos et al, 2005;Fukaya et al, 2013), and we found that exposing 3D-MDCK cyst cultures to PMA induced the internalization of EGFR in vesicles independently of IQGAP1 expression ( Fig 5C). As PMA activation of PKC is thought to mediate signaling through several pathways, we stimulated EGFR with EGF to specifically study the response of this receptor.…”
Section: Egfr Stimulation Induces Iqgap1 Depolarization and Mitotic Ssupporting
confidence: 70%
“…It was previously demonstrated that the phosphorylation of EGFR controls its subcellular distribution in 3D-MDCK cultures, allowing it to modulate epithelial morphogenesis (Cotton et al, 2013). Moreover, PMA phosphorylates and transactivates EGFR in glioblastoma cells and in dermal fibroblasts (Amos et al, 2005;Fukaya et al, 2013), and we found that exposing 3D-MDCK cyst cultures to PMA induced the internalization of EGFR in vesicles independently of IQGAP1 expression ( Fig 5C). As PMA activation of PKC is thought to mediate signaling through several pathways, we stimulated EGFR with EGF to specifically study the response of this receptor.…”
Section: Egfr Stimulation Induces Iqgap1 Depolarization and Mitotic Ssupporting
confidence: 70%
“…This view has recently been challenged by Yoda et al, who showed that the levels of validated ADAM17 substrates were not increased in the serum of ADAM17-overexpressing transgenic mice compared to the wild-type animals, undermining the correlation between ADAM17 expression and its activity [ 35 ]. Nevertheless, systemic overexpression of ADAM17 may have pathological consequences despite the lack of correlation between the level of ADAM17 expression and the plasma levels of its substrates [ 36 ]. Furthermore, tissue-specific deletion or hypomorphic knock-in of Adam17 leads to a decrease in the serum levels of ADAM17 substrates [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells stimulate type I collagen synthesis in fibroblasts in vitro, 20 and excessive accumulation and deposition of type I collagen is associated with dermal fibrosis. 21 24 Hypertrophic scars in both humans and Duroc pigs have been associated with high numbers of mast cells, 25 whereas fewer mast cells are observed in fetal or oral mucosal wounds compared with scar-forming adult dermal wounds. 26 28 …”
Section: Discussionmentioning
confidence: 99%